(Invited) Speciation during Wet Etching of III-V Semiconductors. (15th August 2017) - Hinckley, Adam; Foster, Elijah; Corley, Tim; Muscat, Anthony J.
Abstract : The concentration of volatile arsenic species above GaAs during etching with aqueous HF and HCl was measured via mass spectrometry. The total arsenic detected above solutions with acid concentrations between 0.6 M and 28.9 M was consistently between 4 and 5 mg/m 3 . The mass fragments detected contained As-H and As-O moieties. No volatile species containing gallium were detected. Inductively-coupled plasma mass spectrometry (ICP-MS) was performed on aqueous HF solutions and used with the vapor phase concentrations to close a mass balance on arsenic to within 1-2 nmol. Vapor phase species containing As-O bonds were produced by hydrolysis and increased with etching time. The hydrolysis of these species complicated the identification of specific products in the vapor phase.